Association between Helicobacter pylori infection and mortality risk in prostate cancer patients receiving androgen deprivation therapy: A real‐world evidence study - Jui‐Ming Liu (Wiley, 2021)
Abstract Purpose Helicobacter pylori (H. pylori) is a major risk factor for gastric cancer and may affect androgen activity in men. The association between H. pylori and androgen deprivation therapy (ADT) in patients with prostate cancer (PCa) remains unclear. Methods This retrospective cohort study linked National Health Insurance (NHI) data to Taiwan Cancer Registry (TCR) and Taiwan Death Registry (TDR) between 1995 and 2016. PCa patients who received ADT were classified into H. pylori infection and non‐H. pylori infection groups. The outcomes were overall mortality, prostate cancer‐specific mortality, and castration‐resistant prostate cancer (CRPC). Propensity score matching was adopted for the primary analysis and inverse probability of treatment weighting (IPTW) was used for the sensitivity analysis. Results Of the 62,014 selected PCa patients, 23,701 received ADT, of whom 3516 had H. pylori infections and 20,185 did not. After matching, there were 3022 patients in the H. pylori infection group and 6044 patients in the non‐H. pylori infection group. The mean follow‐up period for the matched cohort was 4.8 years. Compared to the non‐H. pylori group, the H. pylori group was significantly associated with decreased risks of all‐cause mortality (hazard ratio [HR] 0.90; 95% confidence interval [CI] 0.84–0.96) and prostate cancer‐specific mortality (HR 0.88; 95% CI 0.81–0.95) in the matched analysis. Conclusions H. pylori infection was associated with a reduced risk of mortality in PCa patients receiving ADT.